Pengaruh Dividen Payout Ratio, Debt To Equity Ratio, Free Cash Flow, dan Earning Per Share Terhadap Keputusan Perusahaan Melakukan Stock Repurchase Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia tahun 2019 – 2021 - Cristina Andriyati S; Arifah Hidayati; Sintia Safrianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze the effect of the Dividend Payout Ratio, Debt to Equity Ratio, Free Cash Flow and Earning Per Share on the decision to purchase Stock Repurchase in companies listed on the IDX in 2019-2021. The population in this study are go public companies that have repurchased stocks that are listed on the IDX for the 2019-2021 period. The sample in this study amounted to 54 companies that went public. The research design used was quantitative research and the sampling method used in this study was purposive sampling method. The data used in this research is secondary data. The data analysis method used in this study is multiple regression analysis with the help of the IBM SPSS version 25 application program. The results of the analysis show that (1) the dividend payout ratio has no effect on stock repurchase purchasing decisions, (2) the debt to equity ratio has no effect on stock repurchase decisions. purchase of stock repurchase, (3) Free cash flow affects the decision to purchase stock repurchase, (4) Earning per share does not affect the decision to purchase stock repurchase and (5) Dividend payout ratio, Debt to equity ratio, Free cash flow and Earning per share does not influence simultaneously on the stock repurchase purchase decision.